2020
DOI: 10.3389/fphys.2020.00599
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Inhibits Twist-Mediated Renal Tubulointerstitial Fibrosis by Upregulating Id2 Expression

Abstract: The final pathway for the development of diabetic nephropathy (DN) into chronic renal failure in DN is glomerulosclerosis and tubulointerstitial fibrosis. Renal tubular lesions can occur in the early stage of DN renal injury. Cumulative evidence shows that oxymatrine (OMT) has a variety of biological and pharmacological properties. In recent years, more attention has been paid on the preventive and therapeutic influence of OMT on organ fibrosis. In this experiment, db/db mice were intraperitoneally injected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Twist1, as a member of the basic helix–loop–helix family of transcription factors, has multiple functions that are associated with the pathogenesis of fibrotic diseases and tumor progression [ 39 ]. Twist1 signaling is relatively silenced in adult kidneys but can be reactivated in various experimental animal models and in CKD in humans [ 40 ]. Indeed, we found that Twist1 activation was increased in kidneys from IgAN patients with Lee's grade III–V, but was rarely expressed in IgAN patients with Lee's grade I–II (early stage of IgAN, no fibrosis).…”
Section: Discussionmentioning
confidence: 99%
“…Twist1, as a member of the basic helix–loop–helix family of transcription factors, has multiple functions that are associated with the pathogenesis of fibrotic diseases and tumor progression [ 39 ]. Twist1 signaling is relatively silenced in adult kidneys but can be reactivated in various experimental animal models and in CKD in humans [ 40 ]. Indeed, we found that Twist1 activation was increased in kidneys from IgAN patients with Lee's grade III–V, but was rarely expressed in IgAN patients with Lee's grade I–II (early stage of IgAN, no fibrosis).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found in vitro that oxymatrine could inhibit TGF-β1/Smad-mediated EMT in epithelial cells by up-regulating the expression of nuclear transcription co-repressor Ski-related novel protein N [ 68 ]. In addition, it has been found that in diabetic nephropathy mice treated with oxymatrine, the expression of inhibitor of differentiation 2 (Id2) was significantly increased in the kidney, which suggests that oxymatrine may play a role in anti-renal fibrosis by restoring the expression of Id2 and promoting the binding of Id2 and Twist in the damaged kidney thereby regulating the expression of genes downstream of Twist and inhibiting EMT in tubular epithelial cells [ 69 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…In diabetic rats, oxymatrine considerably lowers oxidative stress and the levels of transforming growth factor- β1 (TGF-β1), AGEs, CTGF, and inflammatory cytokines in the kidney [ 55 ]. By increasing Id2 expression, oxymatrine also prevents twist-mediated renal tubulointerstitial fibrosis [ 56 ].…”
Section: Bioactive Phytochemicals For Dnmentioning
confidence: 99%